2010
DOI: 10.1007/s11664-010-1195-3
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Temperature Bonding Process Using Mixed Cu–Ag Nanoparticles

Abstract: A low-temperature bonding process to form joints with high strength and ionic migration resistance using mixed Cu-Ag nanoparticles was studied. Although it was difficult to obtain strong joints using Cu nanoparticles, with the addition of Ag nanoparticles to the Cu nanoparticles the bonding strength of the Cu-to-Cu joints increased. The joints formed by the mixed Cu-Ag nanoparticles at 350°C exhibited a high bonding strength of $50 MPa. Counterelectrodes made of the mixed Cu-Ag nanoparticles had four times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…It is difficult to obtain a dense sintered Ag layer without the bonding pressure. 1,2 The mean bonding strength of the Cu-to-Cu disc joints was clearly improved when using the mixture system of Ag nanoparticles, as shown in Fig. 3.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…It is difficult to obtain a dense sintered Ag layer without the bonding pressure. 1,2 The mean bonding strength of the Cu-to-Cu disc joints was clearly improved when using the mixture system of Ag nanoparticles, as shown in Fig. 3.…”
Section: Methodsmentioning
confidence: 93%
“…[6][7][8][9] The organic layer on the Ag nanoparticles was the same as for the Ag nanoparticles used in our previous study. 2,6 The mean diameter of the Ag nanoparticles was 20.2 nm (small nanoparticles: NP S ), 58.5 nm (medium nanoparticles: NP M ), and 168.0 nm (large nanoparticles: NP L ), respectively. The size and shape of these Ag nanoparticles were relatively uniform, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the ECM tolerance can be improved by using a composite paste made by adding Au and Pd particles to a Ag 2 O paste. 16) Moreover, a bonding process using Cu nanoparticles has been researched 17,18) because it is known that the ECM tolerance of Cu is higher than that of Ag. However, once again these bonding materials still do not reduce the cost to a level sufficient for widespread commercial use.…”
Section: Introductionmentioning
confidence: 99%